THE USE OF CARTOON VIDEO AS A MEDIA TO TEACH DESCRIPTIVE WRITING TEXT TO THE EIGHTH GRADERS OF JUNIOR HIGH SCHOOL (RETAIN, 2014)
THE USE OF CARTOON VIDEO AS A MEDIA TO TEACH DESCRIPTIVE WRITING TEXT TO THE EIGHTH GRADERS OF JUNIOR HIGH SCHOOL Anggi Tri Prasetya Ningtyas 102084224 English Education, Faculty and Language and Art, State University of Surabaya Email: Anggitriningtyas@gmail.com Dra. Theresia Kumalarini, M.Pd. English Education, Faculty and Language and Art, State University of Surabaya email: kumala_rini52@yahoo.co.id Abstrak Manusia menghasilkan bahasa untuk berkomunikasi dengan orang lain . Dalam proses belajar mengajar , para siswa menghadapi banyak masalah dalam belajar bahasa Inggris , terutama dalam mempelajari teks deskriptif . Media video kartun ini adalah alternatif untuk mengajar menulis teks deskriptif akan Mudah jika diterapkan di kelas . Tempat penelitian ini di SMP AL - ISLAM Krian . Penelitian ini menjawab dua pertanyaan penelitian yang dinyatakan sebagai berikut ( 1 ) Bagaimana pelaksanaan video kartun dalam mengajar menulis teks deskriptif untuk siswa kelas VIII SMP AL - ISLAM Krian ? ( 2 ) Bagaimana respon siswa terhadap pelaksanaan video kartun dalam mengajar menulis teks deskriptif ? Dalam penelitian ini , penulis menggunakan penelitian deskriptif kualitatif . Subyek penelitian ini adalah siswa VIII E. Ada tiga jenis instrumen yang digunakan dalam penelitian ini adalah lembar observasi , angket, dan catatan kaki. Penelitian ini dilakukan dalam tiga pertemuan . Dalam setiap pertemuan , guru memberikan tugas di topik yang berbeda , topiknya adalah " Binka and Brave " , "Moving Day " dan " Girl Trouble ". Hasil penelitian ini cukup memuaskan. Selain itu , para siswa tidak mengalami kesulitan mengidentifikasi Generic Structure dan language future teks deskriptif , meskipun guru harus menjelaskan kata kunci dan kosa kata asing dalam setiap pertemuan. Pelaksanaan pembelajaran menggunakan video kartun yang disampaikan berhasil . Dapat disimpulkan bahwa penggunaan kartun video untuk mengajarkan teks deskriptif bisa merangsang ide siswa untuk menulis teks yang baik . Kata Kunci: Video kartun, kemampuan Menulis, Teks Deskriptif Abstract People produce language to communicate with others. In the teaching and learning process, the students face many problems in learning English, especially in learning a descriptive text. This alternative technique to teach descriptive writing text would be easier if cartoon video implemented in the classroom. The setting of this study is at SMP AL-ISLAM KRIAN. This study answered two research questions which were stated as follows: (1) How was the implementation of cartoon video in teaching writing descriptive to the eight grade students of SMP AL-ISLAM Krian? (2) How were the students’ responses towards the implementation of cartoon video in teaching writing descriptive?In this study, the writer used descriptive qualitative research. The subject of the study was 8-F students. There were three kinds of instruments used in this study. The researcher was conducted in three meeting. In every meeting, the teacher gave an assignment in different topics, the topics of which were “Binka and Brave”, “Moving Day” and “Girl Trouble”. The result of the study was satisfactory. Moreover, the students had no difficulty identifying the generic structure and language features of a descriptive text, although the teacher had to explain the keywords and unfamiliar vocabulary in every meeting. The implementation of cartoon video which was generally spoken was successful. It could be concluded that the use of cartoon video to teach a descriptive text could stimulate the students’ idea to write a good text. Keywords: Cartoon Video, Writing Skill, Descriptive Text INTRODUCTION People need interactions each other. Moreover, language is important in communications, without having language, people are isolated and helpless. Dealing with the curriculum, the seventh grade of junior high school students have to master descriptive text. Descriptive text is one of the functional texts. Unfortunately, the students have some problems in writing descriptive text. The students find it difficult to write a correct structure of descriptive text. On the other hands, the researcher found some weaknesses of the teacher in teaching descriptive text to the students. In order to make the students being motivate and enjoy to learn, the teacher should use interesting teaching methods, as Jeremy Harmer (2007: 20) states that teacher’s method in teaching can be intrinsic motivation that motivates the students to learn. Media can be used by both teachers and students. The use of media also allows the students to be involved in the teaching and learning process. Purwati (2002: 25) states: One of the media used in teaching writing is video. Most of audiovisual media make students easily understand and enjoy the lesson in writing class. By using video as media for the teaching of descriptive text, students will be more interested and more active in learning. Because of the reasons above, the researcher wants to conduct an observation study in SMP AL-ISLAM Krian by using cartoon video as a media in teaching descriptive text. Writing is functional communication; making learners possible to create imagined worlds of their own design, it means that, through writing, learners can express thought, feeling, ideas, experiences, etc to convey a specific purpose. The purpose of writing is to give some information. Meyers (2005:2) said that writing is an action. This means that when the students first write something down, they have already been thinking about what they are going to say. Then after the students have finished writing, they read over what they have written and make changes and corrections. Writing is a productive skill, which contains a symbol (orthographic) and involves a complex process. In making a good writing, the students must use correct grammatical rules, choose appropriate vocabulary, and consider the coherent and cohesion. By writing, we can share our idea, feeling, or anything that exist in our mind. Writing prosecutes students to focus on generating idea, organizing coherently, revising it into good composition, using discourse markers and rhetorical conventions cohesively, and editing text for appropriate grammar. Descriptive text is one of the types of writing where the writer describes something: perhaps a place, an object and person. The writer draw us the picture with recreated as recapture sounds, smells, or feeling as near the observation itself as words on a page can create (Depdiknas, 2004:4). The purpose of descriptive text is to tell to the reader about the situation that has been seen clearly, it can make the reader feels that he or she have seen the object by him or herself. It tells and describes a particular person, place or thing. In teaching and learning process, there are several important components that must be fulfilled. Besides, there is another component that should be included. It is something that could help the teacher in the teaching and learning process. It can be called as a media. Media comes from the Latin word “Medium” which means something to deliver the message from sender to the receiver. According to Sadiman et al (2002), media is kind of tools used to deliver information from sender to receivers which can attract their mind, feeling, attention and interest of the students, so that the teaching and learning process happened. It means that media can develop the relation between teacher and students in the teaching and learning process effectively. Media can be used to overcome the students’ boredom. Student will enjoy the teaching and learning process and understand about the material given when they are interested in what they are doing. A video is a technology of capturing, recording, processing, transmitting, and reconstructing motion pictures. That is one of technologies which is popular in people’s daily life. It is used almost in every part of people’s life, such as for entertainment, information, education, etc. Video becomes popular nowadays because educational world also use it as one of the media in the teaching and learning process. There are some reasons why video can be used in this process. First, video can give authentic model of the language. It means that the students who are watching video can directly observe how intonation can match facial expression (Harmer, 2002:282). Video is considered as good thing to see the English culture. It shows how people live thing, and behaves in the culture. Derewianka states that a descriptive text can be learned through video (1990:32). It is said that the students will get enthusiastic and motivated to learn something, if the material learned are suitable with their development. In choosing the material, teacher should be selective, it must be in line with the students need, student interest in accordance with the students’ development video stimulates students, and students will pay more attention in learning language. Harmer (2001:261) said that the principal roles in writing task should be motivate students on creating the right condition for generating ideas, so they will write easily. In order to exploit the video fully in the classroom, the teacher should integrate pre-viewing, viewing, and post viewing activities into the lesson. METHODOLOGY Research Subjects Research was a descriptive qualitative research designed to describe the teaching learning process which was taken place in natural setting of classroom. Qualitative research is a research taken in natural setting of the classroom and emphasized on the result of the research in the form of narrative explanations to give understanding and meaning (Mcmillan, 1992: 9). The researcher was the observer in this research. The data of the research were collected through observation checklists, questionnaires and field notes. In this research, the researcher took notes based on everything she saw and heard in the class during the teaching learning process. At the end of teaching learning process, the teacher and observer did the reflection based on the observation checklists. After reflecting the teaching learning process, the next step was exchanged the information of the situation happened in class. In this case, the teacher and observer discussed the information of teaching learning process based on observation checklists and field notes. The subject of the study was the students of the eight grade of Junior High School. The researcher took class 8F of SMP AL-ISLAM KRIAN (YAPALIS). It was consisted of 43 students, included 22 boys and 21 girls. Instrument of the Study In this study, the main instrument to collect the data was the writer herself. It was in line with Marriam (1998: 7) who stated that in qualitative research the researcher was the primary instrument for data collection and analysis. In this research, the researcher observed, paid attention, took notes on the activities happened in class to set the data needed. In order to collect the data, the researcher used several instruments. They were as follows: observation checklists, field note and questionnaire. Data Collection Data collection technique is a way to get the research data. In this research, the data collection techniques consisted of observation checklists, questionnaires, and field notes. The research was conducted in three meetings. This data were the result of observation checklists. The data collected from observation checklists and field notes were used to answer research question number 1 which was questioned about the implementation of using cartoon video in teaching writing of descriptive text to the eight grade students of SMP AL-ISLAM Krian. Furthermore, in order to answer research question number 2 which was questioned about the students’ responses toward the implementation of using cartoon video in teaching writing of descriptive text, the researcher used questionnaires. Data Analysis Technique The data of this study was analyzed by descriptive qualitative research design. The data was obtained during and after the data collection phase. The researcher presented the result of the observations and students’ opinions in descriptive manner. She presented the data in the form of descriptions. She described the result of the observations to her questions in the checklists. Furthermore, the researcher described the result of the observation which was obtained from the class condition, the teacher’s activities in leading this technique, and also the students’ activities in the classroom. The researcher organized all the data based on the observations, synthesized the data, and decided what to report. She summarized the data critically and explained the data logically. RESULT The Results of the First Observation The researcher conducted the first observation on February 6th 2014. At that time, the class began at 11.00 am and ended at 12.30 pm. There were three activities in each meeting namely Pre-viewing Activities, Viewing, and Post-viewing Activities. 1. Pre-viewing Activity The teacher checked the attendance lists; one student was absent that day, there were 42 students who attended the class. She greeted the students. The students raised their hands as their name being called. Then the teacher asked about the student’s feeling that day. The students enjoyed the little chat with the teacher before starting the lesson. 2. Viewing-activities The teacher gave an example of a descriptive text. She asked the students to read it. The teacher also asked the students whether it was a good example of descriptive text before the teacher used a video as media to teach descriptive text. 3. Post-activities The teacher reminded the students that there was a time limit for writing the descriptive text. When the time was up the teacher asked the students to submit their works. After that, the teacher and the students reviewed the lesson that day. The Results of the Second Observation 1. Pre-activities The second observation was held on February 8th 2014. The class started at 07.00 am and ended at 08.30 am. The activities in the second observation were almost the same as the first observation. The writing class was held in the classroom. 2. Viewing-activity In this step, the teacher introduced a new topic that she had already prepared. The topic was “Moving Day” cartoon video by Mickey Mouse and Donald Duck (see appendix 6). In this video, there were mentioned some things: kinds of T-shirt, table, piano, cupboard, etc. In this activity, the teacher explained what the students should do which was similar with the first meeting. She asked the students to pay attention to the video carefully. 3. Post-activities The teacher asked the students to submit their work. In this step, the teacher made sure that all of the students had done their writing. The teacher asked the students about their feeling after they wrote descriptive text. The students said that they wrote better than the previous meeting. At the end of the day, the teacher greeted and ended the lesson. The Results of the Third Observation 1. Pre – activities It was started by greeting and asking the students about the previous lessons. It aimed to know whether the students were still remembered about the material in the previous lessons 2. Viewing – activity In this part, the teacher explained the activities while watching cartoon video. There were some opinions from the students about the cartoon video. The class was active enough and there were interaction between students and teacher. 3. Post-activities The teacher limited the time when the students wrote a descriptive text based on cartoon video and when the time was up the teacher asked the students to submit their work DISCUSSION. The Implementation of Using Cartoon Video in Teaching Writing of Descriptive Text The researcher used questionnaire to collect the data for the second research question. The researcher spread out questionnaire to find out the students’ opinion on the use of cartoon video in writing text. The data then were used as the basis on knowing the success of the use of cartoon video in writing descriptive text. When the questionnaire was spread out, forty students joined the class, three students were absent. Here are the results of the students’ responses toward questionnaire. Question number one until four were asking about the material and lesson in descriptive text. Most of the students agreed that the teacher explained the material clearly. It was proved by the result, half of the students agreed that the material presented by the teacher in front of the class was easy to understand. Therefore, the students did not find any difficulties in understanding descriptive text. And then some of students they answered about very agreed that descriptive text was easy. Question number five until ten were asking about the use of cartoon video to teach descriptive text. Most of the students’ greed that they enjoyed the material in descriptive text by using cartoon video. And then half of students agreed that the cartoon video in teaching process was clearly helpful. The next result was about the responses in the process of the use cartoon video in teaching descriptive text. More than a half agree that the use of cartoon video can generate their ideas in writing descriptive. Therefore, the students did not have difficulties to understand about the material when the teacher using cartoon video, about half of the students chosen that answer. The last questionnaire was focusing on the students’ interest in use of cartoon video more than students agreed that the use of cartoon video to teach descriptive text was successful to create enjoyable atmosphere in the classroom. Not only the teacher’s role which influenced student’s writing, but also the material and media used in the learning and teaching descriptive writing text. Dealing with the implementation of cartoon video, most students liked that very much. The class atmosphere showed that the students were enthusiastic when they were watching cartoon video. It was effective to make the students felt relaxed and enjoyed in the learning and teaching writing. It was in line with Arcario and Stempleski (1994: 110) who stated that the video used in teaching and learning activity should be suitable with students’ interest. They enjoyed the video very much because it was very funny and entertaining. In short, the use of cartoon video was very helpful to attract the students’ interest, raised their motivation, and helped them generating ideas. Using video in good condition was very important to help the students understand of the video itself. CONCLUSION AND SUGGESTIONS Conclusions In this study, it is found that the implementation of using cartoon video in teaching writing of descriptive text is effective. It helps the students write descriptive text easily. There are three meetings in the teaching writing of descriptive text using cartoon video. All videos used in every meeting have different topics to present. The teacher always explains the students about the relevant keywords related to the videos. These activities help the students to write descriptive texts. Moreover, the students really enjoy writing descriptive text using cartoon video as media. Teacher’s explanations also help the students in the learning process. Although the students have some difficulties in mastering grammars, vocabularies, and organization, but they have solutions to overcome these difficulties. Suggestions Based on the result of the research, there are still many aspects that should be revised. The teacher and other researchers can make the revision in teaching learning process of writing descriptive text to the students. Some suggestions are presented as follows: For the Teacher Concerning the students’ difficulties in getting the ideas of writing, the researcher suggests that: The topic should be interesting and familiar to the students, neither too easy nor too difficult in order to motivate the students in writing. Moreover, using a familiar topic makes the students be able to choose proper words and organize them into correct sentences in descriptive text. In writing class, the teacher is suggested to use cartoon video to help the students arrange ideas, organize ideas, and focus on the topic given while they are expressing their ideas freely. For the Researcher The teaching and learning process using cartoon video gives opportunities to other researchers to develop this study since there are still many areas to be explored by using cartoon video. The study on the use of cartoon video can be conducted in the other language skills such as listening, speaking, and reading. Other researchers can also use follow up technique if they find the result of this research is unsatisfactory. REFERENCES Alan Meyers.(2005). Gateways to Academic Writing: Effective Sentences, Paragraphs, and Essays, (New York: Pearson Education, Inc), p. 2 Andersons, Mark, and Kathy Andersons. (2003). Text Type in English 1-2, Australia:MacMillan Education. Arikunto, Suharsimi.( 1998 ): Prosedur Penelitian : Suatu Pendekatan Praktek. Jakarta: Rieneka Cipta. Brown, H Douglas.(1994). Teaching by principle: an interactive approach to language pedagogy. New Jersey: Prentice Hall Chau, E.(2003). Developing beginner language skills through video. AMEP Conference. Claude W.Faulkner.(1950). Writing Good Sentences, (New York:Charles Scribner’s Sons),p.1 David Nunan and Clarice Lamb. (1996). The Self-Direct Teacher. Managing the Learning Process,(Cambrdge: Cambridge University Press), p. 14. Depdiknas. (2004). Kurikulum 2004 Standart Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menengah Pertama dan Madrasah Tsanawiyah.Jakarta:Depdiknas. Derewianka, Beverly. (1990). Exploring how text works. Marlborough: Australia Print Group. Harmer, Jeremy. (2002). The practice of English language teaching 3 rd edition. England : Pearson education Limited. Harmer Jeremy. (2001) . The practice of English language teaching 3 rd edition. England: person education Limited. Harmer Jeremy. (2007). How To Teach Writing, (England: Longman),p. 33 Heaton, J.B. (1991) Writing English Language Test. New York: Longman Jack C Richard.(1990). The Language Teaching Matrix,(New York: Cambridge University Press), p.100 Mcmillan, James H. (1992). Educational Research: Fundamental for the consumers. New York: Harper Collins Publishers. Purwati, Dian. (2007). Media Pembelajaran. Jakarta: Rajawali Pers. Purwati, Oikurema. (2007). Model Pembelajaran dan Media pembelajaran.Surabaya: UNESA Richard Kern. (2000). Literacy and Language Teaching, (New York: Oxford University Press), p. 172 Rosa, Alfred and Elcholas, Paul. (1986). Model for Writer: Short essay for composition. New York: St. Martin;s press Setyadik, Trival. (2007). The Implementation of Teaching Writing Through Semantic Mapping of Descriptive Text in SMP. Unpublished Thesis. Universitas Negeri Surabaya. Sherman, J. (2003). Using authentic Video in the language classroom. Cambridge: Cambridge University Press Stempleski. S & Barry,Tomalin. (1990). Vidio IN Action : recipes for Using Video in Language Teaching.Great Britain : Prentice Hall, Inc. Stempleski, Susan, and Paul Arcario, eds (1994). Video in second language teaching: using, selecting and producing video for classroom. New York: TESOL Inc Stoller, Fredericka L. (1990). Film and Video tapes in the Content based ESL/EFL Classroom. Washington: FPG Inc. Syamsuddin. (2007). Metode Penelitian Pendidikan Bahasa.Bandung: PT. Remaja Rosdakarya Offset White, Fred D. (1986). The Writer’s Art. A Practical Rhetoric and Handbook, (New York: Wadsworth Publishing Company.